Osobennosti intuicii vysokokvalificirovannych sportsmenov - Vasileva, I. V.; Grigoriev, P. E.; Matvienko, S. V.; Zimina, T. V. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2016)
The purpose of the study was to show that extreme, physically and emotionally intensive character of professional sport activity influences on the intuition features of athletes. To assess the intuition copyright software "Anticipation of affective stimuli" were used (by P.E. Grigoriev, I.V. Vasileva, A.A. Taratukhin). The following results were obtained: athletes anticipate affective incentives more quickly rather than neutral. Gender differences in intuition disappear in athletes because women are oriented on mental activity in the same way as men. Intuitiveness of tested subjects is maximal at the beginning of the experiment, it is consistent with earlier observations of other researchers. Conclusion: the particularities of the sports activities affect the features of the implementation of intuition.